PRESENTASE KANDUNGAN MINYAK HASIL PENYULINGAN LDPE TERHADAP KARAKTERISTIKNYA - Saifudin Asngari; Muh Malyadi; Wawan Trisnadi Putra (Universitas Muhammadiyah Ponorogo, 2019)
Plastic oil is a fuel produced from plastic, which is processed by means of distillation. In the plastic distillation process used LDPE (Low density polyethylene) plastic bag, this type of plastic is ductile and flexible in addition to this type of plastic also has a transparent nature, and is resistant in shock so that this type of plastic is widely used by the community for plastic wrapping. LDPE plastic is included in the type of thermoplastic is one of a group of plastics that are able to be recycled again so that it is easy in the distillation process. The results of diesel oil plastic types will be mixed with bio diesel and tested for density, color, distillation, flash point, sulfur content and cetane number values. In a mixture of 30% LDPE plastic type diesel oil and 70% bio diesel with a density of 843.3 kg / m3, has a clear and bright color, in the distillation process in a mixture of 30% LDPE plastic type diesel oil 70% bio diesel is known at initial temperatures IBP 150oC at 10% drop at 201oC at 50% drop at 289oC and at the last drop 90% at 347oC. a mixture of 30% LDPE plastic type diesel oil and 70% bio diesel has a flash pont value with 57oC test results. sulfur content in a mixture of 30% LDPE plastic type diesel oil and 70% bio diesel with a value of 0.11% m / m, in a mixture of 30% LDPE plastic type diesel oil and 70% bio diesel has a cetane number value of 53oC.